Demonstration of quantum volume 64 on a superconducting quantum computing system - Jurcevic, Petar; Javadi-Abhari, Ali; Bishop, Lev S; Lauer, Isaac; Bogorin, Daniela F; Brink, Markus; Capelluto, Lauren; Günlük, Oktay; Itoko, Toshinari; Kanazawa, Naoki; Kandala, Abhinav; Keefe, George A; et al. (Quantum science and technology, 2021)
We improve the quality of quantum circuits on superconducting quantum computing systems, as measured by the quantum volume (QV), with a combination of dynamical decoupling, compiler optimizations, shorter two-qubit gates, and excited state promoted readout. This result shows that the path to larger QV systems requires the simultaneous increase of coherence, control gate fidelities, measurement fidelities, and smarter software which takes into account hardware details, thereby demonstrating the need to continue to co-design the software and hardware stack for the foreseeable future.